Sistem Monitoring Kekeruhan Air Berbasis IoT (Studi Kasus : Perumda Ende) - Yunita Arsyad; Benediktus Yoseph Bhae; Kristianus Jago Tute (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
Currently, the Ende Regency PERUMDA is still using the manual turbidity meter monitoring system. This causes the low quality of clean water. This problem prompted the author to conduct research by creating a new system, namely An air turbidity monitoring system created using a website-based system and the Internet of Things. The device used in the manufacture of this system is a turbidity sensor as a water turbidity detector by reading the optical properties of water. In addition to the turbidity sensor, there is another device, namely the ESP 8266 which functions as an open source micro controller, this device can be used in the development of Internet of Things projects. An automatic turbidity monitoring system is expected to assist in the process of monitoring water turbidity. In order to complete the IoT-based Water Turbidity Monitoring System Design, conduct research based on specific, detailed, and clear methods. This method is used by researchers with data analysis techniques using statistics. In this research, the system design or development method used is Rapid Application Development. The Rapid Application Development method is a software development process that designs and implements information systems so as to produce a short, concise, and solid development cycle. The beginning of this test is to ensure that the implementation of the designed water turbidity monitoring software can work properly according to the program.